2006
DOI: 10.1158/0008-5472.can-06-0171
|View full text |Cite
|
Sign up to set email alerts
|

Defective Oxidative Phosphorylation in Thyroid Oncocytic Carcinoma Is Associated with Pathogenic Mitochondrial DNA Mutations Affecting Complexes I and III

Abstract: Oncocytic tumors are characterized by cells with an aberrant accumulation of mitochondria. To assess mitochondrial function in neoplastic oncocytic cells, we studied the thyroid oncocytic cell line XTC.UC1 and compared it with other thyroid non-oncocytic cell lines. Only XTC.UC1 cells were unable to survive in galactose, a condition forcing cells to rely solely on mitochondria for energy production. The rate of respiration and mitochondrial ATP synthesis driven by complex I substrates was severely reduced in X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
194
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 205 publications
(209 citation statements)
references
References 45 publications
10
194
1
1
Order By: Relevance
“…Two samples (Table 1) harbored the same mutation (3571insC) in the ND1 gene that we recently reported in the XTC.UC1 oncocytic cell line, in which we demonstrated complete absence of the protein and defective activity of complex I (10).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Two samples (Table 1) harbored the same mutation (3571insC) in the ND1 gene that we recently reported in the XTC.UC1 oncocytic cell line, in which we demonstrated complete absence of the protein and defective activity of complex I (10).…”
Section: Resultssupporting
confidence: 76%
“…Recently, we have attempted to clarify this point by clearly demonstrating the association between mtDNA mutations and defective oxidative phosphorylation in a cell line model of thyroid oncocytic tumor (10). The term ''oncocytic'' is used to designate lesions composed of cells with aberrant accumulation of mitochondria, resulting in a distinctive granular eosinophilic appearance on conventional histology.…”
mentioning
confidence: 99%
“…Renal oncocytoma, another type of oncocytic tumour with a benign course, was recently found to be associated with complex I deficiency (Gasparre et al, 2008;Mayr et al, 2008). The oncocytic tumour cell line XTC.UC1, which is derived from a metastasis of a Hürthle cell carcinoma, shows both an insertion mutation in the gene encoding ND1 subunit of complex I and a reduction in complex I activity (Bonora et al, 2006). Ishikawa et al (2008) reported complex I deficiency caused by mutations in the ND6 gene of complex I in non-oncocytic mouse lung tumours.…”
Section: Discussionmentioning
confidence: 99%
“…An association between mitochondrial DNA (mtDNA) mutations and oncocytic thyroid tumours was reported in several studies (Tallini et al, 1994;Maximo et al, 2002;Bonora et al, 2006). A study on 45 oncocytic thyroid tumours identified potentially pathogenic mutations in subunits of complex I (NADH-ubiquinone oxidoreductase) in 53% of the investigated samples (Gasparre et al, 2007).…”
mentioning
confidence: 92%
“…Warburg averred that an irreversible injury to respiration had to occur in order to trigger the progressive striving of cells that had succeeded to engage in lactic fermentation to fulfill their energy needs, leading ultimately to the formation of a tumor (Warburg, 1956a). Mutations in mitochondrial DNA (Bonora et al, 2006), and defective mitochondrial lipid content and structure (Kiebish et al, 2008), were found to squelch respiration in some tumors, while malfunction of some Krebs cycle enzymes also contributes to apoptosis resistance and aerobic glycolysis (King et al, 2006). This suggests that mitochondrial defects may have a role in certain cancers.…”
Section: Perspectivesmentioning
confidence: 99%